2013
DOI: 10.1016/j.neuroscience.2013.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-proprioceptive interactions in degenerative cervical spine diseases requiring surgery

Abstract: Cervical proprioception plays a key role in postural control, but its specific contribution is controversial. Postural impairment was shown in whiplash injuries without demonstrating the sole involvement of the cervical spine. The consequences of degenerative cervical spine diseases are underreported in posture-related scientific literature in spite of their high prevalence. No report has focused on the two different mechanisms underlying cervicobrachial pain: herniated discs and spondylosis. This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Li et al [21] also reported good results following more extensive cervical surgery. Freppel et al [4] KEY POINTS Cervicogenic vertigo/dizziness is probably common, but it lacks a validated clinical test.…”
Section: Degenerative Cervical Disorders and Vertigomentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [21] also reported good results following more extensive cervical surgery. Freppel et al [4] KEY POINTS Cervicogenic vertigo/dizziness is probably common, but it lacks a validated clinical test.…”
Section: Degenerative Cervical Disorders and Vertigomentioning
confidence: 99%
“…This is logical as injuries to the neck might disturb the difficult adjustment between the two coordinate systems of the head and body [36]. Freppel et al [4] reported that the contribution of visual input to postural control was reduced in patients operated on for degenerative cervical spine disorders. Freppel et al [4] reported that the contribution of visual input to postural control was reduced in patients operated on for degenerative cervical spine disorders.…”
Section: Diagnostic Tests For Cervicogenic Vertigomentioning
confidence: 99%
“…A convincing mechanism of cervical vertigo is based on altered upper cervical somatosensory input associated with neck ten-derness and limitation of movement (7,13). Interstitial inflammatory mediators have been postulated to sensitize muscle spindles (37), and myofascial trigger points exhibit spontaneous electromyogram activity, which is compatible with hyperactive muscle spindles (38). Neck proprioception has been studied previously in patients with cervical vertigo as individuals with whiplashassociated unsteadiness and/or dizziness were shown to have significantly greater joint position errors and more severe neck pain than control subjects (27).…”
Section: Proprioceptive Cervical Vertigomentioning
confidence: 99%
“…Short-term benzodiazepines or antidepressants may improve emotional symptoms (1). Some studies report excellent outcomes after cervical spine surgery (5,22,23). However, it remains unreasonable to perform cervical spine surgery for CV lacking other indications for surgery.…”
mentioning
confidence: 99%
“…Among the various causes of vertigo, the so-called cervicogenic vertigo (CV) has been the most controversial (1). However, there is clear experimental and clinical evidence that neck perturbations or purely proprioceptive signals can induce vertigo and imbalance (1,(3)(4)(5). Different pathophysiological mechanisms have been attributed (1) and many definitions are given for CV, some of which require pain and others that do not (6).…”
mentioning
confidence: 99%